2013
DOI: 10.1063/1.4774328
|View full text |Cite
|
Sign up to set email alerts
|

Direct current plasma jet at atmospheric pressure operating in nitrogen and air

Abstract: Toroidal magnetized plasma device with sheared magnetic field lines using an internal ring conductor Rev. Sci. Instrum. 84, 013504 (2013) Energy distribution of electron flux at electrodes in a low pressure capacitively coupled plasma J. Appl. Phys. 113, 023306 (2013) A simple class of singular, two species Vlasov equilibria sustaining nonmonotonic potential distributions Phys. Plasmas 20, 012107 (2013) Collisional and collective effects in two dimensional model for fast-electron transport in refluxin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
87
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 143 publications
(100 citation statements)
references
References 26 publications
3
87
0
1
Order By: Relevance
“…The nanocomposite films are deposited using an atmospheric pressure plasma deposition system with a nitrogen direct current (DC) plasma jet as shown in Figure a. The plasma is generated between a pin and a mesh electrode placed in a quartz tube . Investigation based on optical emission spectroscopy revealed that plasma contains abundant excited states of nitrogen molecules (N 2 (A 3 Σ, B 3 Π, C 3 Π)) and ionized species (normalN2+ (B 2 Σ u , X 2 Σ g )).…”
Section: Methodsmentioning
confidence: 99%
“…The nanocomposite films are deposited using an atmospheric pressure plasma deposition system with a nitrogen direct current (DC) plasma jet as shown in Figure a. The plasma is generated between a pin and a mesh electrode placed in a quartz tube . Investigation based on optical emission spectroscopy revealed that plasma contains abundant excited states of nitrogen molecules (N 2 (A 3 Σ, B 3 Π, C 3 Π)) and ionized species (normalN2+ (B 2 Σ u , X 2 Σ g )).…”
Section: Methodsmentioning
confidence: 99%
“…Room temperature atmospheric pressure plasma jets (RT‐APPJs) have attracted widespread attentions in the last decade due to their applications such as biomedicine and material processing . Researchers found out that the plasma plumes looks like continuously by naked eyes are actually bullets like volumes of plasmas traveling at a speed of 10 4 –10 5 m s −1 .…”
Section: Introductionmentioning
confidence: 99%
“…; Deng et al . ):normalO2+normaleO+O+eO+normalO2+MnormalO3+MnormalN2+normalO2normalN2+2OnormalN2+normalO2normalN2O+OO+normalN2NO+OO+NO+MNO2+Mwhere M=O, O 2 or O 3 , a third collision partner. Based on the experimental results, elemental oxygen played an essential role in inducing the reactive species to influence an interaction with the micro‐organism (Guo et al .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the high sterilization efficiency was mainly attributed to oxygen radicals, ozone and nitrogen oxide. The formation of oxygen radicals and nitrogen oxide can be described by the following reactions (Eliasson et al 1987;Hill and Smoot 2000;Ahn et al 2003;Deng et al 2013):…”
Section: Assessment Of the Effects Of Various Inactivation Agents On mentioning
confidence: 99%